2012
DOI: 10.1039/c2jm33440b
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Sr0.95Ce0.05CoO3−δ loaded with copper nanoparticles as a bifunctional catalyst for lithium-air batteries

Abstract: Sr 0.95 Ce 0.05 CoO 3Àd (SCCO) particles loaded with copper nanoparticles on their surface are shown to be excellent, low-cost, and stable bifunctional catalysts for the oxygen-reduction and oxygen-evolution reactions (ORR and OER) in aqueous solution. Evidence for the presence of Ce 3+ and Co 2+ as well as Co 4+ and Co 3+ ions revealed by XPS measurements as well as XRD analysis indicates that a CeCoO 2.5 brownmillerite phase may be extruded to the surface. A surface Co 4+ /Co 3+ couple is known to be a good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 40 publications
2
104
0
Order By: Relevance
“…The first spin-orbit doublet, having a binding energy of the 2p3/2 level of 779.1-780.6 eV and Δ = 2p3/2 -2p1/2 splitting of 15.1eV, is characteristic of the octahedral Co 3+ component, in agreement with our previous description for similar related oxides [38]. The peaks appearing at 780.3-780.5 eV with Δ splitting of 15.3 eV could be assigned to Co 4+ as reported in the literature for mixed metal oxides [39,40].…”
Section: +supporting
confidence: 77%
“…The first spin-orbit doublet, having a binding energy of the 2p3/2 level of 779.1-780.6 eV and Δ = 2p3/2 -2p1/2 splitting of 15.1eV, is characteristic of the octahedral Co 3+ component, in agreement with our previous description for similar related oxides [38]. The peaks appearing at 780.3-780.5 eV with Δ splitting of 15.3 eV could be assigned to Co 4+ as reported in the literature for mixed metal oxides [39,40].…”
Section: +supporting
confidence: 77%
“…To a certain degree, all of these researches have evidenced the promising application of NiCo 2 O 4 as efficient electrocatalyst in Li-O 2 battery. Simultaneously, these researches also highlights the importance of favorable cathode structure and intrinsically high catalytic activity of cathode material, which is further supported by Zhu et al [123] In detail, they reported a new electrode structure constituted of vertically aligned carbon nanosheets and metal hydroxide (M(OH) x @CNS) hybrid arrays, integrating [126][127][128][129][130][131] However, in many cases, perovskite catalysts obtained by conventional synthesis methods have quite low intrinsic electronic conductivities and small specific surface areas, which lead to low catalytic activity, thus limiting their usage. Therefore, to improve the performance of the perovskite materials in Li-O 2 batteries, a variety of modification methods were employed, including (a) combination of ABO 3 with conductive nanocarbons such as carbon black, carbon nanotube, and graphene to enlarge the effective contact area for catalysis and improve the electrical conductivity of the perovskite oxide/carbon electrodes; (b) synthesis of porous-structured perovskites with increased number of oxygen pathways and specific surface area to enhance the catalytic performance.…”
Section: Noble Metal Metal Oxides and Other Electrocatalystsmentioning
confidence: 66%
“…It can be seen that the charge transfer and diffusion processes of the Ca 9 Co 12 O 28 cathode are both superior to those of the Ca 3 Co 4 O 9 cathode. The Co 3þ/4þ couple is known to be a good catalyst for the oxygen-reduction and oxygenevolution reactions [31,49] …”
Section: Electrochemical Performancementioning
confidence: 99%